RETRACTED: Identification of hub genes and construction of prognostic nomogram for patients with Wilms tumors - Lou, Lei; Chen, Luping; Wu, Yaohao; Zhang, Gang; Qiu, Ronglin; Su, Jianhang; Zhao, Zhuangjie; Lu, Zijie; Liao, Minyi; Deng, Xiaogeng (Frontiers in Oncology, 2022)
Background In children, Wilms' tumors are the most common urological cancer with unsatisfactory prognosis, but few molecular prognostic markers have been discovered for it. With the rapid development of high-throughput quantitative proteomic and transcriptomic approaches, the molecular mechanisms of various cancers have been comprehensively explored. This study aimed to uncover the molecular mechanisms underlying Wilms tumor and build predictive models by use of microarray and RNA-seq data. Methods Gene expression datasets were downloaded from Therapeutically Applicable Research to Generate Effective Treatments (TARGET) and Gene Expression Omnibus (GEO) databases. Bioinformatics methods were utilized to identified hub genes, and these hub genes were validated using qPCR. Nomogram predicting OS was developed using genetic risk score model and clinicopathological variables. Results CDC20, BUB1 and CCNB2 were highly expressed in tumor tissues, especially CDC20. This may reveal molecular biology features and a new therapeutic target of Wilms tumour.7 genes were selected as prognostic genes after univariate, Lasso, and multivariate Cox regression analyses and had good accuracy, a prognostic nomogram combined gene model with clinical factors was completed with high accuracy. Conclusions The current study discovered CDC20,BUB1 and CCNB2 as hub-genes associated with Wilms tumor, providing references to understand the pathogenesis and be considered a novel candidate to target therapy and construct novel nomogram, incorporating both clinical risk factors and gene model, could be appropriately applied in preoperative individualized prediction of malignancy in patients with Wilms tumor.